Predictive Factors for ICU and Ward Stay After CABG - Fereydoun Sabzi; Abdolrasoul Moloudi (Journal of Tehran University Heart Center, 2006)
Background: To determine factors that predicts ICU and ward stay during hospitalization for coronary artery surgery.